If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 7x = -1y Solving 4 + 7x = -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 7x = -4 + -1y Combine like terms: 4 + -4 = 0 0 + 7x = -4 + -1y 7x = -4 + -1y Divide each side by '7'. x = -0.5714285714 + -0.1428571429y Simplifying x = -0.5714285714 + -0.1428571429y
| 2x+4=-3x-21 | | 1-8x=-2x-11 | | -54r-27p+36= | | 4(x+1)=4[x-(2-x)] | | -9+2x=7x-5-7x | | -6x=10-x | | -7(a+2)+15=1-7a | | 2-y=x-6 | | 2-(15-7)*7= | | 3-3=0.03703703703 | | 8-5+2-4+7*6= | | 1-0.75x-0.3x^2=0 | | e=3(8)+3(8) | | 5(t-3)-2t=3t-8 | | 5y+29=5+25 | | -8+5r=5r-r | | 18=21x-6y | | 99+5x=2000+-5x+911 | | 75-50x+6x^2=0 | | 15f-8f+13=-14 | | -7-7n=-6n-2n | | -32f-12g=48 | | 2(9-7s)= | | -5*y=x^2 | | 2r-y-6=0 | | 4k(7k+5)= | | 12b^2-8=6b | | X+(-4)=-7 | | -10+2x=3x-1+8x | | 12b^2-8=ab | | x^2(x+7)=40x+100 | | (y^2)-23y+130=0 |